2014
DOI: 10.1177/1524839914543105
|View full text |Cite
|
Sign up to set email alerts
|

Consumer Understanding of Calorie Labeling

Abstract: Many people do not know the daily recommended caloric intake. Public education on the government calorie reference value is necessary for menu-labeling interventions to be more effective. Weekly text messaging can serve as an effective modality for delivering calorie information and nutrition education.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 30 publications
0
1
1
1
Order By: Relevance
“…The results revealed that African American women have favorable views toward seeking mental health services, comparable with non-African American women [27]. Our findings are contrary to the results of a previous study by Watson and Hunter who found that African American women have less favorable attitudes toward professional help seeking than their non-African American counterparts [3].…”
Section: Principal Findingscontrasting
confidence: 99%
See 1 more Smart Citation
“…The results revealed that African American women have favorable views toward seeking mental health services, comparable with non-African American women [27]. Our findings are contrary to the results of a previous study by Watson and Hunter who found that African American women have less favorable attitudes toward professional help seeking than their non-African American counterparts [3].…”
Section: Principal Findingscontrasting
confidence: 99%
“…To our knowledge, there have been no studies that have examined the acceptability of text messaging to help African American women manage anxiety or depression. Nonetheless, prior studies that included a representative sample of African American participants (>13% of the study sample) and used text messaging for weight management, physical activity, or prenatal care education interventions have been effective [27][28][29][30]. Therefore, the insufficient representation of African Americans in previous telemental health studies may be largely because of ineffective recruitment and retention strategies, in addition to the previously discussed barriers that prevent them from seeking mental health care [31,32].…”
Section: Introductionmentioning
confidence: 99%
“…Vários fatores intrínsecos ao consumidor estão associados, como renda, escolaridade, patologias, necessidades individuais, sexo, entre outros. Mas os resultados podem ser afetados também pelas variações nos desenhos dos estudos, com intenção de escolha versus escolha real, tipo e localização das informações calóricas e dependência de dados alimentares autorrelatados ou obtidos a partir da venda dos alimentos, não podendo ser avaliado o consumo real (ABEL et al, 2014).…”
Section: Estudos Experimentais Com Escolha Real Dos Alimentosunclassified